Software para la gestión de la autoevaluación para el proceso de acreditación de los programas académicos de la Corporación Universitaria de la Costa (2012)
This thesis proposes the design, development, training and deployment of a web platform as a support tool to manage and evaluate quickly and simultaneously the different actors involved in a self-evaluation. This software allows you to store all the necessary information for self-evaluation process, also trace it and facilitates the collection of statistics that provide an analysis, which is necessary to give some judgments that will define how far an academic program of excellence is in terms of education’s quality. For the development of the platform we achieved the integration of two major market frameworks: Joomla and ExtJS. The first one gives us all the libraries for the ACL, session management, mail and application logic. And the other one offers us a variety of web’s controls which interact to the server, with an asynchronously way from the browser to make queries and storages in the database without reloading the web page, adding to the usability of the software. Through this project we replaced the pencil, paper or Excel macros that try to be instruments for the surveys implementations; for a complete web platform which is going to be scalable, concurrent, stable, secure and easily accessible